Tunable Narrow-Linewidth Ring Laser Based on the Polarization Conversion in a Tapered Fiber-Coupled Whispering Gallery Mode Resonator - Pengfa Chang (MDPI AG, 2021)
Based on the polarization conversion in a tapered fiber-coupled whispering gallery mode (WGM) system, a simple-structured narrow linewidth band-pass filter was fabricated and a narrow linewidth ring laser was demonstrated. With a fiber Bragg grating (FBG) to further select the resonant mode, the ring laser could be in the single-longitudinal-mode with the linewidth about 6 kHz and its wavelength could be tuned from 1540.10 nm to 1570.01 nm. Benefit from the dense modes in the WGM resonator, high conversion efficiency, and better stability of the structure, a tunable dual-wavelength laser could be achieved based on two FBGs with different resonant wavelengths. The configuration of the proposed laser is simple and stable, which will benefit its applications in the future.